Inhibition of Tumor Cells Interacting with Stromal Cells by Xanthones Isolated from a Costa Rican Penicillium sp. - Cao, Shugeng (2012)
CR1642D, an endophytic isolate of Penicillium sp. collected from a Costa Rican rainforest, was identified through a high-throughput approach to identify natural products with enhanced antitumor activity in the context of tumor–stromal interactions. Bioassay-guided separation led to the identification of five xanthones (1–5) from CR1642D. The structures of the xanthone dimer penexanthone A (1) and monomer penexanthone B (2) were elucidated on the basis of spectroscopic analyses, including 2D NMR experiments. All of the compounds were tested against a panel of tumor cell lines in the presence and absence of bone marrow stromal cells. Compound 3 was the most active, with IC50 values of 1–17 μM, and its activity was enhanced 2-fold against tumor cell line RPMI8226 in the presence of stromal cells (IC50 1.2 μM, but 2.4 μM without stromal cells).